(untitled) (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
Traditional games are an integral part of a community’s cultural heritage, serving not only as entertainment but also as instruments for character building, cultural identity reinforcement, and the transmission of core values across generations. In Riau Province, particularly among the Malay ethnic group, several traditional games reflect deep-rooted local wisdom, including cakbur, setatak, and taki karet. However, the rapid advancement of digital technology and the increasing influence of foreign cultures have caused these games to gradually fade from everyday life, especially among younger generations. This study aims to introduce, describe, and document these three traditional games as a strategic effort to preserve and revitalize local cultural practices. The research employs a qualitative descriptive method with an ethnographic approach, involving direct observation, in-depth interviews with cultural figures and game practitioners, and visual documentation. The findings reveal that cakbur emphasizes physical agility and competitiveness, setatak promotes balance and teamwork, while taki karet enhances creativity and fine motor skills in children. All three games demonstrate strong potential to be integrated into formal and informal educational activities as culturally grounded educational tools. Preserving these traditional games is crucial not only for safeguarding the cultural identity of the Malay Riau community but also as a form of cultural resilience against the forces of global homogenization.